2013
DOI: 10.1002/2013jc009231
|View full text |Cite
|
Sign up to set email alerts
|

Origin and pathways of Winter Intermediate Water in the Northwestern Mediterranean Sea using observations and numerical simulation

Abstract: The study of water masses worldwide (their formation, spreading, mixing, and impact on general circulation) is essential for a better understanding of the ocean circulation and variability. In this paper, the formation and main pathways of Winter Intermediate Water (WIW) in the Northwestern Mediterranean Sea (NWMED) are investigated during the winter‐spring 2011 using observations and numerical simulation. The main results show that the WIW, formed along the continental shelves of the Gulf of Lion and Balearic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 50 publications
8
46
0
Order By: Relevance
“…The WIW can also be formed on the continental shelves of the Gulf of Lions and the Balearic Sea [Vargas-Yañez et al, 2012;Juza et al, 2013].…”
Section: Eddies Characterization and Classification 321 Anticyclonmentioning
confidence: 99%
“…The WIW can also be formed on the continental shelves of the Gulf of Lions and the Balearic Sea [Vargas-Yañez et al, 2012;Juza et al, 2013].…”
Section: Eddies Characterization and Classification 321 Anticyclonmentioning
confidence: 99%
“…As highlighted by Heslop et al (2012), Juza et al (2013) and in Fig. 11a, the 504 observed T/S diagram reveals the typical water masses of the WMED (AW, LIW, WMDW) and the 505 presence of WIW in the Ibiza Channel at 50-200m (Fig.…”
mentioning
confidence: 90%
“…11d). Juza et al (2013) have shown, using 506 a regional high-resolution simulation, that the main part of the WIW going through the Ibiza 507…”
mentioning
confidence: 99%
“…Based on historical data, the mean potential temperature and salinity of the core in summer in the Sardinian Sea are 17.71 • C and 37.61 with a standard deviation of 2.87 • C and 0.33, respectively (Sparnocchia et al, 1994). WIW consists of cooled and homogenized MAW formed in winter during cold wind events in the northern WMED (Juza et al, 2013). It is characterized by local minima in potential temperature and salinity at about 150 to 200 m depth, with magnitudes depending on the formation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…WIW mainly follows the path of MAW westward along the European continental slope and across the Algerian Basin (Millot, 1999;Benzohra and Millot, 1995). An additional pathway of WIW directly connecting the formation area to the Algerian Basin is expected to be induced by frontal eddies associated with the North Balearic Front (Millot, 1999;Fuda et al, 2000). This North Balearic Front separates the Atlantic Water reservoir in the south from the saltier and denser waters in the north (Olita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%